Considerations for an Alternative Site of Islet Cell Transplantation. (March 2020) - Addison, Poppy; Fatakhova, Karina; Rodriguez Rilo, Horacio L.
Islet cell transplantation has been limited most by poor graft survival. Optimizing the site of transplantation could improve clinical outcomes by minimizing required donor cells, increasing graft integration, and simplifying the transplantation and monitoring process. In this article, we review the history and significant human and animal data for clinically relevant sites, including the liver, spleen, and kidney subcapsule, and identify promising new sites for further research. While the liver was the first studied site and has been used the most in clinical practice, the majority of transplanted islets become necrotic. We review the potential causes for graft death, including the instant blood-mediated inflammatory reaction, exposure to immunosuppressive agents, and low oxygen tension. Significant research exists on alternative sites for islet cell transplantation, suggesting a promising future for patients undergoing pancreatectomy.